2022
DOI: 10.1128/jmbe.00289-21
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates' Experiences with Online and in-Person Courses Provide Opportunities for Improving Student-Centered Biology Laboratory Instruction

Abstract: Biology laboratory courses with hands-on activities faced many challenges when switched to online instruction during the COVID-19 pandemic. The transition back to in-person instruction presents an opportunity to redesign courses with greater student input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…While stand-alone exercises may work, introducing students to a diverse tool kit allows them to engage with scientific evidence in a variety of formats. The Investigative Biology Laboratory course ( 2 ) at Cornell University has been using this multistep method in the past 8 years (5,703 students) along with science communication training. In the end-of-semester evaluations, on a 5-point scale students estimated a 1.06 ± 0.2 point (mean ± standard deviation), statistically significant improvement ( t = −24.0, df = 28.6; P < 0.001) in their science literacy and science communication skills ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While stand-alone exercises may work, introducing students to a diverse tool kit allows them to engage with scientific evidence in a variety of formats. The Investigative Biology Laboratory course ( 2 ) at Cornell University has been using this multistep method in the past 8 years (5,703 students) along with science communication training. In the end-of-semester evaluations, on a 5-point scale students estimated a 1.06 ± 0.2 point (mean ± standard deviation), statistically significant improvement ( t = −24.0, df = 28.6; P < 0.001) in their science literacy and science communication skills ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To make informed decisions, undergraduates need to learn how to become effective consumers of information, understand the nature of science, and make connections across the science, technology, engineering, and mathematics (STEM) fields ( 1 ). Introductory biology laboratory courses have components of science literacy training ( 2 ) and equip students with the skills to consume and produce scientific information ( 3 ). Instead of a stand-alone exercise, we promote a multistep framework ( Table 1 ) to teach science literacy skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hight et al (2021) demonstrated that social media videos could facilitate student-centered learning and public engagement through projectbased learning activity. Similarly, Sarvary et al (2022) found that online learning through technological devices and in-person courses provide opportunities for improving studentcentered Biology laboratory instruction. Moreover, Turdieva and Olimov (2021) and Wang and Song (2022) disclosed that games technology is an innovative type of studentcentered learning, and provided significant contribution in developing students' autonomous learning.…”
Section: Introductionmentioning
confidence: 98%
“…But this online transition comes with new pedagogical and cognitive costs for students and teachers alike (Pokhrel and Chhetri, 2021 ; Psotka, 2022 ). And while there is some early scholarly evidence on the learning experiences of students in online environments (Almendingen et al, 2021 ; Flores et al, 2022 ; Kuntz and Manokore, 2022 ; Orlov et al, 2021 ; Raaper et al, 2022 ; Sarvary et al, 2022 ; Warfvinge et al, 2022 ), teachers’ emotions and views about online teaching methods remain largely unexplored (Bartlett, 2021 ; Jones and Kessler, 2020 ). We contribute to fill this gap in the literature by designing and administering an online survey experiment to 444 educators of a large social sciences university in the United Kingdom to evaluate their experiences on the effectiveness of online teaching methods.…”
Section: Introductionmentioning
confidence: 99%